2005
DOI: 10.1016/j.molcel.2005.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Nuclear Export Receptor Cse1 in Its Cytosolic State Reveals a Closed Conformation Incompatible with Cargo Binding

Abstract: Cse1 mediates nuclear export of importin alpha, the nuclear localization signal (NLS) import adaptor. We report the 3.1 A resolution structure of cargo-free Cse1, representing this HEAT repeat protein in its cytosolic state. Cse1 is compact, consisting of N- and C-terminal arches that interact to form a ring. Comparison with the structure of cargo-bound Cse1 shows a major conformational change leading to opening of the structure upon cargo binding. The largest structural changes occur within a hinge region cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 30 publications
4
82
0
Order By: Relevance
“…They found that, mainly driven by electrostatic interactions, the structure of Cse1p spontaneously collapses and adopts a conformation close to the experimentally determined cytoplasmic form within a relatively short timescale of 10 ns. Simulations of mutants with different electrostatic surface potentials did not reveal a significant conformational change but remained in an open conformation which is in good agreement with experimental findings (Cook et al 2005). This example shows that functionally relevant conformational changes that occur on short time scales can be studied by MD simulations.…”
Section: Nuclear Transport Receptorssupporting
confidence: 88%
“…They found that, mainly driven by electrostatic interactions, the structure of Cse1p spontaneously collapses and adopts a conformation close to the experimentally determined cytoplasmic form within a relatively short timescale of 10 ns. Simulations of mutants with different electrostatic surface potentials did not reveal a significant conformational change but remained in an open conformation which is in good agreement with experimental findings (Cook et al 2005). This example shows that functionally relevant conformational changes that occur on short time scales can be studied by MD simulations.…”
Section: Nuclear Transport Receptorssupporting
confidence: 88%
“…This region is potentially solvent exposed and is close to the region that undergoes a major conformational change on binding of cargo. 29 Interestingly, in addition to CAS, we also detected an interaction between the SID and the N-terminal 165 amino acids of NUP93 (Fig. 1A), which localises to the nuclear basket of the nuclear pore complex.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to the fact that Exp5 undergoes a transition to an extended state after dissociation of its binding partners, the exportin CAS/Cse1p is more compact in the unbound state than in the ternary export complex. It is suggested that the presence of an intra-molecular interaction, which constrains the karyopherin superhelix in a tight ring-shape structure, seals off the cargo-binding sites, keeping cargo from rebinding to CAS/Cse1p in the cytosol (Cook et al 2005;Zachariae and Grubmüller 2006).…”
Section: Discussionmentioning
confidence: 99%